QUALITY OF THE ELDERLY AND AVAILING OF NON-FOOD-BASED NATIONAL SOCIAL ASSISTANCE SCHEMES IN INDIA: A CROSS-SECTIONAL STUDY - Lo, Sourav; Pramanik, Rama; Biswas, Daliya (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2024)
Background: Health and quality of life (QOL) are crucial constituents. In providing social safety for older people, the weakening social support system and rising burdens are having huge impact. Purpose: To assess the QOL of old age people and their relationship with availing of non-food-based social assistance schemes. Methods: This was a descriptive community-based study which was conducted in urban slums of Bankura district, West Bengal among all individuals aged ≥60 years fulfilling inclusion and exclusion criteria. WHOQOL-BREF questionnaire was used for assessing QOL. Results: A total of 107 participants were recruited for the study. Most common morbidities were hypertension, diabetes mellitus, chronic bronchitis, etc. The majority (80.5%) of participants were receiving non-food-based NSAS for less than 10 years. Overall QOL was ‘Good’ in 69.2% of study subjects. Most of the elderly had ‘Good’ QOL in Physical, Psychological, Social, and Environment domains. Participants availing non-food-based NSAS had good physical, social, environmental health of QOL and overall QOL. Conclusion: Despite good QOL among the elderly, appropriate and relevant health indicators need to be developed.